Fertilizer and Weed Management Options for Direct Wet Seeded Rice in Dry Season (Bangladesh Rice Journal, 2016)
Direct seeding of rice is an emerging technology. However, direct seeded rice culture in the main field is hindered by enormous weed infestation and it lacks judicious fertilizer management. So, experiments were conducted during dry seasons of 2010 and 2012 with three fertilizer packages and four weed control measures. Rice seed was sown in the field using drum seeder in wet soil. The results revealed that weed density and weed biomass were strongly influenced by weed control methods and fertilizer rates. Weed density was higher in unweeded plots with 140:36:43 kg NPK ha-1. Among the species Echinichloa crusgalli (L.) P. Beauv. was the dominant species. Three hand weeding controlled maximum weeds. Uses of herbicide for controlling weeds were above 80 and 70% effective. Strong negative correlation was recorded between grain yield and weed density. Herbicide with one hand weeding and BRRI weeder in combination with 160:46:53 kg NPK ha-1 produced about 81- 104% higher grain yield than no weeding. Weed free plot produced 112% higher yield with 160:46:53 kg NPK ha-1. Besides, herbicide with one hand weeding and BRRI weeder treated plot produced similar yield irrespective of fertilizer doses. The strong positive and linear relationship was found in case of yield and yield components. Herbicide with one hand weeding and 120:26:33 kg NPK ha-1 gave higher net return (1145 $/ha). The benefit cost ratio was also higher in herbicide based weed management with reduced rate of fertilizer. Direct seeded culture using herbicide with one hand weeding and 120:26:33 kg NPK ha-1 could be an option for reducing production cost in dry season along with satisfactory grain yield.Bangladesh Rice j. 2016, 20(1): 65-75